2012
DOI: 10.1177/0363546512453300
|View full text |Cite
|
Sign up to set email alerts
|

The Biomechanical and Histologic Effects of Platelet-Rich Plasma on Rat Rotator Cuff Repairs

Abstract: Background Rotator cuff tears are common injuries that are often treated with surgical repair. Because of the high concentration of growth factors within platelets, platelet-rich plasma (PRP) has the potential to enhance healing in rotator cuff repairs. Hypothesis Platelet-rich plasma would alter the biomechanical and histologic properties of rotator cuff repair during an acute injury response. Study Design Controlled laboratory study. Methods Platelet-rich plasma was produced from inbred donor rats. A t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
108
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(112 citation statements)
references
References 41 publications
4
108
0
Order By: Relevance
“…PRP collagen fibers were more organized and thicker than in the control. Aside from slight infiltration by hypertrophic chondrocytes during the first 7 days, the PRP treatment did not have any negative effects but did not aid or accelerate healing [86].…”
Section: Prp For Acute Tendinopathiesmentioning
confidence: 84%
“…PRP collagen fibers were more organized and thicker than in the control. Aside from slight infiltration by hypertrophic chondrocytes during the first 7 days, the PRP treatment did not have any negative effects but did not aid or accelerate healing [86].…”
Section: Prp For Acute Tendinopathiesmentioning
confidence: 84%
“…In addition, when different factors are added they inhere the potential to differentiate into tenocytes [77][78][79][80][81][82] . Animal studies revealed that both, PRP and MSCs, have the potential to improve histological and biomechanical properties of regenerated tendons [29][30][31]71,72,75,[91][92][93]95,97,98 . Application of MSCs even resulted in regeneration of the enthesis in a rat model 7,91,92 .…”
Section: Discussionmentioning
confidence: 99%
“…Application of MSCs even resulted in regeneration of the enthesis in a rat model 7,91,92 . Although the benefits from PRP seemed to be encouraging in preclinical studies [28][29][30][31] , PRP failed to prove significant, reproducible impact on regeneration in patients [42][43][44][45][46][48][49][50][51][52] . This is the reason why further studies are needed to improve the capabilities of the PRP use 54 .…”
Section: Discussionmentioning
confidence: 99%
“…In an experiment in which rats were treated for RCT, the group given the PRP treatment demonstrated better collagen linear alignment. Furthermore, the research team found positive effects when administering the PRP injections 3 weeks after the initial surgery [76].…”
Section: Laboratory Investigationmentioning
confidence: 99%